Internet Based Services and Their Impact on Postgraduate Students Patronage of University Library (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The purpose of this study was to examine internet-based services and their impact on post-graduate students’ patronage of University Library. Three research questions and three null hypotheses were formulated to guide the study. Related literatures were reviewed while the study adopted descriptive survey research design. The sample size of 174 post graduate students who are users of University of Uyo library was used while A researcher structured questionnaire titled “Internet-Based Services and their Impact on Post Graduate Students Patronage of University of Uyo Questionnaire” (IBSIPGSGQ) was used for the study. The questionnaire was subjected to face validity by by experts in LIS and Test and measurement for appropriateness of the instrument. Cronbach Alpha reliability coefficient was used to test the reliability of the instrument using 20 post graduate students from Akwa ibom state University which did not form a part of the sample. The reliability test gave a high coefficient of 0.76 which show that the instrument was reliable for the study. The data generated for this study were analyzed using mean and standard deviation to answer the research questions, while independent t-test statistical methods was used in testing the null hypotheses at 0.05 level of significant. The findings of the study revealed that there is significant influence of internet-based services such as information search service, data-based service, and web-based reference service on post graduate students’ patronage of university of Uyo library. Based on the findings of the study, it was recommended among others that data-based service should be made availability in all higher institution libraries so as to assist the PG students in obtaining research information.